Fish intake during pregnancy, fetal growth, and gestational length in 19 European birth cohort studies. Issue 3 (11th December 2013) - Leventakou, Vasiliki; Roumeliotaki, Theano; Martinez, David; Barros, Henrique; Brantsaeter, Anne-Lise; Casas, Maribel; Charles, Marie-Aline; Cordier, Sylvaine; Eggesbø, Merete; van Eijsden, Manon; Forastiere, Francesco; Gehring, Ulrike; et al.
ABSTRACT: Background: Fish is a rich source of essential nutrients for fetal development, but in contrast, it is also a well-known route of exposure to environmental pollutants. Objective: We assessed whether fish intake during pregnancy is associated with fetal growth and the length of gestation in a panel of European birth cohort studies. Design: The study sample of 151, 880 mother-child pairs was derived from 19 population-based European birth cohort studies. Individual data from cohorts were pooled and harmonized. Adjusted cohort-specific effect estimates were combined by using a random- and fixed-effects meta-analysis. Results: Women who ate fish >1 time/wk during pregnancy had lower risk of preterm birth than did women who rarely ate fish (≤1 time/wk); the adjusted RR of fish intake >1 but <3 times/wk was 0.87 (95% CI: 0.82, 0.92), and for intake ≥3 times/wk, the adjusted RR was 0.89 (95% CI: 0.84, 0.96). Women with a higher intake of fish during pregnancy gave birth to neonates with a higher birth weight by 8.9 g (95% CI: 3.3, 14.6 g) for >1 but <3 times/wk and 15.2 g (95% CI: 8.9, 21.5 g) for ≥3 times/wk independent of gestational age. The association was greater in smokers and in overweight or obese women. Findings were consistent across cohorts. Conclusion: This large, international study indicates that moderate fish intake during pregnancy is associated with lower risk of preterm birth and a small but significant increase in birth weight.